Competition and commercial banks risk-taking: evidence from Sub-Saharan Africa region. Issue 44 (20th September 2018) - Akande, Joseph Olorunfemi; Kwenda, Farai; Ehalaiye, Dimu
ABSTRACT: This study investigates the relationship between competition and the risk-taking attitude of banks. We test how this relationship manifests in the Sub-Saharan African(SSA) region's commercial banks in light of the competition-fragility view, using the generalized methods of moments. We studied 440 commercial banks in 37 SSA countries over the period 2006–2015. The results provide evidence that supports a positive relationship between competition and banks' overall risk as well as their credit risk but suggests that off-balance sheet risk reduces with competition. We, therefore, conclude that the propensity to undertake higher risk in a competitive banking environment largely accounts for fragility as argued in the competition-fragility view.